Resource characteristics of the scads, Decapterus ruseelli and D. macrosoma of the Vizhinjam area, southwest coast of India - Balasubrahmanian, N X; Natarajan, P (Indian Journal of Fisheries, 2011)
Resource characteristics of the two commercially important scada Decapterusrusselli and D. macrosoma were studied at Vizhinjam area from 1993 to 1995.Detailed analyses were made on catch composition among carangids, catch-CPUE relations of these species and total carangids in different gear-craftcombinations, and the efficiency of these gear units on the catch of thesespecies. D. russelli dominated the carangid fishery followed by D. macrosomaaveraging 30 and 10 percentages respectively. Hooks and line gear operatedfrom mechanised crafts was found to be the most efficient gear for carangids,in particular for D. russelli. A comparison was made between the catch ratesof the different gear-craft combinations in the two species. These results arediscussed highlighting the effect of mechanisation on the catch and catch rateand suggest stock assessment to check whether the stock of these commerciallyimportant species are overexploited.